Práticas alimentares de discentes usuários de um restaurante Universitário em Belém/Pa - SILVA, Karina Puga da (2023)
The objective of this study was to analyze the eating practices of University Restaurant (UR) users in terms of their eating behavior. This is a descriptive study with a quantitative approach, applied to students at the Federal University of Pará, UR users, in Belém/PA, between October 17th and 31st, 2022. A form was applied addressing: Personal data; Academic information; Socioeconomic profile and Habits that influence Food and Eating Behavior. The sample consisted of 359 students, 49.03% from 17 and 21 years old, of which 34.26% were enrolled in the day shift. From the sample, 57.66% were quota students and 78.27% did not have academic aid. Regarding meals, 47.35% attended the UR only during lunch and 83.84% preferred homemade food. 75.21% of the sample were satisfied with the dessert portion, 71.03% with the rice portion, 68.52% with the farofa portion, 67.97% with the beans portion and 66.85% with the salad portion. Proteins obtained 66.57% of satisfaction and 33.43% of dissatisfaction, which 74.17% reported compensating for this lack by serving a larger volume of side dishes or starts. It is concluded that the adopted eating practices are influenced by the academic routine and conditions offered by the institutions. The restaurant guarantees nutritionally safe meals and is a familiar environment for the students' food preferences. Despite obtaining satisfactory percentages, the food choices are influenced by compensatory attitudes, implying disordered eating behavior.